A LEXICAL STUDY ON NON STANDARD EXPRESSIONS IN STUDENTS’ FACEBOOK - Wienny Ardriyati (Dinamika Bahasa dan Budaya, 2012)
It’s a qualitative descriptive approach dealing with mostly words in statuses as its main concern to find out the kinds of non standard expressions used by the students of Language Studies and non Language Studies. There are 350 statuses and were found 447 words of non standard expressions which were based non standard guideline expressions and lexical categories. The findings show that in using the non standard expression between the university students in language faculty and non language faculty are not too distinctive, whereas the major and minor lexical categories occurred in each status of students’ face book.  The frequencies of the occurrence of the non standard expressions are 36.69 % for the language faculty, 36.47 % economics, 16.11 % technology and information technology, and 8.28 % law faculty.   Key words: non standard, variety, frequency, face book, lexical categories